The 4th NextGen Therapies for SJIA and MAS: part 1 the elephant in the room: diagnostic/classification criteria for systemic juvenile idiopathic arthritis and adult-onset still's disease - Peter A. Nigrovic; Fabrizio de Benedetti; Yukiko Kimura; Daniel J. Lovell; Sebastiaan J. Vastert (BMC, 2024)
Abstract Currently, the criteria used to classify patients with SJIA are different from those used for AOSD. However, it has been recognized that the existing terms are too narrow, subdividing the Still's population unnecessarily between pediatric-onset and adult-onset disease and excluding an appreciable group of children in whom overt arthritis is delayed or absent. Government regulators and insurers rely upon the guidance of subject experts to provide disease definitions, and when these definitions are flawed, to provide new and better ones. The classification session at the NextGen 2022 conference helped to serve this purpose, establishing the need for a revised definitional system that transcends the fault lines that remain in existing definitions.